Segmentation of Customers of Horticultural Non-food Products in Southern Germany - Andreas Gabriel; Klaus Menrad (German Journal of Agricultural Economics (GJAE), 2013)
The paper aims to identify clusters of buyers of horticultural products (non-food sector) in Germany based on behavioral factors as well as to determine the relevance of the different discriminatory variables. Data were obtained from 320 face-to-face interviews conducted in Southern Germany. Cluster and discriminant analysis were used to analyze the data. Eight clusters of buyers of horticultural products are identified which show significant differences concerning their socio-demographic characteristics, purchase behavior and buying motives. Gender and the affirmation of the respondent to purchasing or non-purchasing bed, balcony or potted indoor plants are the most important discriminatory variables. The differing behavior and interests of the eight consumer clusters allows fine-tuning of marketing activities of horticultural products within the analyzed distribution channels. Traditional retail shops should aim to attract younger consumers in future. The paper extends previous consumer research by identifying consumer cluster for horticultural products based on behavioral factors.
Keywords: 330; Konsumentenverhalten; Marktsegmentierung; Einzelhandel; Süddeutschland